Analisis Faktor-Faktor Yang Mempengaruhi Minat Beli Remaja Di Watsons Margo City Terhadap Produk Emina - Muhammad Devin; Erni Puspitasari; Irgy Prasetya Agustina (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Based on the data from the questionnaire, this study aims to see the difference in average scores between the two groups. The first group has an average score of 48 with a minimum score of 15 and a maximum of 60. The second group has an average score of 79 with a minimum score of 25 and a maximum of 100. Each group has a standard deviation that shows significant variation in results; the first group has a standard deviation of 8 and the second group has a standard deviation of 14. The variation in results is also higher in the second group, indicating that the group has greater diversity. These results suggest that the second group has factors that influence higher scores. Demographic, psychological, or environmental characteristics may be the cause. The results of this study provide a basis for additional analysis aimed at finding components that overall influence these differences.